Investigation of Crown Fuel Bulk Density Effects on the Dynamics of Crown Fire Initiation in Shrublands - Tachajapong, Watcharapong; Lozano, Jesse; Mahalingam, Shankar; Zhou, Xiangyang; Weise, David R (Combustion science and technology, 2008)
Crown fire initiation is studied by using a simple experimental and detailed physical modeling based on Large Eddy Simulation (LES). Experiments conducted thus far reveal that crown fuel ignition via surface fire occurs when the crown base is within the continuous flame region and does not occur when the crown base is located in the hot plume gas region of the surface fire. Accordingly, the focus in this article is on crown fuel ignition when the crown base is situated within the intermittent flame region. In this region, the flame shape and height changes with time over the course of pulsation. This causes the flame to impinge on the crown fuel base and the hot gas is forced through the crown fuel matrix. Under certain conditions, it is observed that the crown fuel bulk density affects the impingement of flame and the ignition of crown fire. The crown fuel properties used were estimated for live chamise (Adenostoma fasciculatum) with a fuel moisture content of 44% (dry basis). As the crown fuel bulk density is increased from 0.75 kg·m-3 to 1.75 kg·m-3, it is observed that the average hot gas velocity inside the crown matrix decreases from 0.70 m·s-1 to 0.52 m·s-1, thus, resulting in less entrained air passing through the crown fuel and more energy accumulation inside the crown fuel matrix. Higher bulk density also influences the surface fire. As the hot gas flows into the crown fuel matrix is retarded, the average hot gas temperature at the crown fuel base increases from 768 K to 1,205 K. This is because the mixing rate of air and combustible gas around the base of crown fuel increases. Although higher fuel bulk density means more fuel must be heated, the increase in accumulated energy per unit volume within the crown fuel matrix is higher than the additional heat needed by the fuel. Thus, the average crown fuel temperature increases and ignition occurs at higher bulk density.